Evaluation of Training Session Applying Gagne’s Events of Instructions - Islam, Nurul; Salam, Abdus (Bangladesh Journal of Medical Science, 2019)
Background: This study explores the effectiveness of educator's training programs regarding the presentation, materials, facilities, relevance and usefulness of the training to the current employment and facilitator’s knowledge using Gagne’s event of instructions. Method: A half day long training was conducted on September 2017 at reach of the two health care teaching institutes. At the end of training, evaluation was done and rated in 5 point Likert scale with 5 as the highest score. Participants agreed that the training was useful and relevant to their work. Result: This study showed a positive perception of the learners which will help their job performance as well as the outcome of their dental teaching school and Gagne’s Events of Instructions can be used when conducting this type of training sessions. Conclusion: Regular training program for staff development need to be carried out following a system approach with right mix of input and contents which process with right sequences of instructions to fill the gap between desired performance and actual staff performance. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.552-556